TIMP-2 Fusion Protein with Human Serum Albumin Potentiates Anti-Angiogenesis-Mediated Inhibition of Tumor Growth by Suppressing MMP-2 Expression - Lee, Mi-Sook; Jung, Jae-In; Kwon, Seung-Hae; Lee, Sang-Mok; Morita, Kyoji; Her, Song (PLOS ONE, 2012)
TIMP-2 protein has been intensively studied as a promising anticancer candidate agent, but the in vivo mechanism underlying its anticancer effect has not been clearly elucidated by previous works. In this study, we investigated the mechanism underlying the anti-tumor effects of a TIMP-2 fusion protein conjugated with human serum albumin (HSA/TIMP-2). Systemic administration of HSA/TIMP-2 effectively inhibited tumor growth at a minimum effective dose of 60 mg/kg. The suppressive effect of HSA/TIMP-2 was accompanied by a marked reduction of in vivo vascularization. The anti-angiogenic activity of HSA/TIMP-2 was directly confirmed by CAM assays. In HSA/TIMP-2-treated tumor tissues, MMP-2 expression was profoundly decreased without a change in MT1-MMP expression of PECAM-1-positive cells. MMP-2 mRNA was also decreased by HSA/TIMP-2 treatment of human umbilical vein endothelial cells. Zymographic analysis showed that HSA/TIMP-2 substantially decreased extracellular pro-MMP-2 activity (94–99% reduction) and moderately decreased active MMP-2 activity (10–24% reduction), suggesting MT1-MMP-independent MMP-2 modulation. Furthermore, HSA/TIMP-2 had no effect on in vitro active MMP-2 activity and in vivo MMP-2 activity. These studies show that HSA/TIMP-2 potentiates anti-angiogenic activity by modulating MMP-2 expression, but not MMP-2 activity, to subsequently suppress tumor growth, suggesting an important role for MMP-2 expression rather than MMP-2 activity in anti-angiogenesis.